Response of giving local microorganism solutions from bamboo shoot to growth and production of red chili plant (Capsicum annum L) jenggo F1 - Hilwa Walida; Eko Surahman; Fitra Syawal Harahap; Wiwit Arif Mahardika (Jurnal Pertanian Tropik, 2019)
Efforts to increase the production of chilli plants are still experiencing obstacles. The presence of several pests and diseases makes one of the limiting factors that cause a decrease in the production of red chili. Likewise, the intensification of plants by fertilizing and applying pesticides continuously at high doses causes deterioration or decreased soil fertility, so that the addition of fertilizer and pesticide inputs are no longer able to spur increased crop productivity. The aim of this study was to determine the response of giving Local Microorganism (MOL) Solutions bamboo shoot to the growth and production of red chili (Capsicum annum L) varieties of Jenggo F1. This research was conducted with 4 doses of MOL bamboo shoot treatment and repeated 10 times. Research data was the averages data of each parameter and then analyzed descriptively. The highest average height of plants at M2 treatment (100 ml / sample) at the age of 10 MST was 44.05 cm. The average number of leaves at M2 treatment (100 ml / sample) aged 10 MST as many as 77.8 strands. The fastest flowering age was35.7 days (M2). The largest initial production weight was 28.50 grams (M2). Giving MOL solution of bamboo shoot at a dose of 100 ml / sample gave a good response to all observed parameters such as plant height (cm), number of leaves (strands), age of flowering (days), and initial production weight (g).